Analisis Pengaruh Work-Family Conflict terhadap Kinerja Dan Komitmen Organisasi (Studi pada Perawat Perempuan di RSUD Soedirman Kebumen) - Ircham Dwi Kurnia; Andita Sayekti (Jurnal Manajemen Kesehatan Indonesia, 2022)
Work-Family-Conflict is a conflict that usually occurs in the female nursing profession, especially for those who are married, this is caused by a mismatch between role pressures from work and family so that it can affect their performance and organizational commitment. The purpose of the study was to analyze the effect of work-family conflict on the performance and organizational commitment of female nurses in Soedirman General Hospital at Kebumen City.The sample of this research is female nurses with married status who work in Soedirman General Hospital at Kebumen City with a total of 41 people. This study uses primary and secondary data sources as well as a quantitative research approach with the technique of determining the sample using purposive sampling and collecting sample data using a questionnaire. The method of analysis used descriptive analysis and associative analysis. Based on this study, it was found that work-family conflict had a negative and significant effect on the performance of female nurses and work-family conflict had an insignificant effect on the organizational commitment of female nurses in Soedirman General Hospital at Kebumen City.